Investigation of the heat shock gene Hsp70 polymorphism in different sheep genotypes - Nagy, Krisztina; Kovács, András; Gyimóthy, Gergely; Oláh, János; Egerszegi, István; Nedambale, Lucky T.; Demberel, Shirchingtyn; Presicce, Giorgio Antonio; Dinnyés, András; Jávor, András; Kusza, Szilvia (Acta Agraria Debreceniensis, 2012)
Nowadays the climate change has an increasing effect on the animals. The warming climate brings up several problems on the area of the animal husbandry, which ones are really important. From the first time the living beings have defensive mechanisms against the heat shock. In current examination we use– from Hungary and from other countries collected –samples of sheep breeds, which are living on different climate. Our fundamental assumption was, that the animals living on other climate adapted to the changes of the environment and there are differeces in their genetic background. These fixed mutations we are looking for in the HSP70 heat shock gene, but we haven’t found any polymorphism yet. We are going to involve further breeds and more individuals in the investigations.